Spatial distribution characteristics of soil organic matter in different land uses and its coupling with soil animals in the plateau basin in the South China Karst basin - Wang, Xingfu; Huang, Xianfei; Zhu, Xun; Wu, Nayiyu; Zhang, Zhenming; Liu, Yi; Huang, Yu; Hu, Jiwei (Frontiers in Environmental Science, 2024)
Karst landforms are widely distributed in southern China. The terrain and soil properties in karst basins are complex, which results in high spatial heterogeneity of the ecological environment and soil organic matter (SOM) in karst watersheds. To investigate the spatial distribution characteristics of SOM in different land uses in the karst plateau basin, a total of 3816 soil samples were taken from 568 soil profiles. The soil animals and different soil properties were recorded, and the concentration of SOM was tested using the potassium dichromate method in the laboratory. Then, the changes in the SOM content associated with soil animals and the soil properties associated with the different land use types were analyzed. The results showed that there was a large discrepancy in SOM in the karst plateau basin, and the average values of SOM in different soil layers were between 9.23 g•kg-1 and 59.39 g•kg -1 . The SOM decreased in the following order: Forestland > grassland > barren land > cultivated land > garden land. The SOM in soil in which soil animals are present is generally greater than that in the absence of soil animals, and the SOM partially increases with soil species diversity. Agrotis segetum is the main soil animal species that positively affects the soil organic matter distribution in the surface soil layer. The SOM in soil with the phylum Annelida is much greater than that in soils with other animals, and earthworms are the main contributor. The structure of soil animal species is complex, and the change trend of SOM is stable. The major positive factors affecting soil animal diversity are soil thickness, soil humidity and soil structure, and rock outcrops are the main negative factor. In summary, good land use can increase animal diversity and abundance in soil, which promotes soil organic matter accumulation. Moreover, microtopography is an important factor that influences soil organic matter accumulation in karst basins and further affects the restructuring of the spatial distribution of soil organic matter.